Biogenic zinc selenide nanoparticles fabricated using Rosmarinus officinalis leaf extract with potential biological activity - Shahram Ahmadi Somaghian; Seyedeh Zahra Mirzaei; Mohammad Ebrahim Khosravi Shakib; Abdolrazagh Marzban; Sarah Alsallameh; Hamed Esmaeil Lashgarian (BMC, 2024)
Abstract Zinc selenide nanoparticles (ZnSe) are semiconductor metals of zinc and selenium. ZnSe NPs are advantageous for biomedical and bio-imaging applications due to their low toxicity. ZnSe NPs can be used as a therapeutic agent by synthesizing those using biologically safe methods. As a novel facet of these NPs, plant-based ZnSe NPs were fabricated from an aqueous extract of Rosmarinus officinalis L. (RO extract). Physiochemical analyses such as UV-visible and FTIR spectroscopy, SEM-EDX and TEM Imaging, XRD and DLS-Zeta potential analyses confirmed the biological fabrication of RO-ZnSe NPs. Additionally, Ro-ZnSe NPs were investigated for their bioactivity. There was an apparent peak in the UV-visible spectrum at 398 nm to confirm the presence of ZnSe NPs. FTIR analysis confirmed RO-extract participation in ZnSe NPs synthesis by identifying putative functional groups associated with biomolecules. TEM and SEM analyses revealed that RO-ZnSe NPs have spherical shapes in the range of 90-100 nm. According to XRD and EDX analysis, RO-ZnSe NPs had a crystallite size of 42.13 nm and contain Se and Zn (1:2 ratio). These NPs demonstrated approximately 90.6% antioxidant and antibacterial activity against a range of bacterial strains at 100 µg/ml. Antibiofilm activity was greatest against Candida glabrata and Pseudomonas aeruginosa at 100 g/ml. Accordingly, the IC50 values for anticancer activity against HTB-9, SW742, and HF cell lines were 14.16, 8.03, and 35.35 g/ml, respectively. In light of the multiple applications for ZnSe NPs, our research indicates they may be an excellent option for biological and therapeutic purposes in treating cancers and infections. Therefore, additional research is required to determine their efficacy.